PENGARUH SELF AWARENESS TERHADAP MOTIF MENGONSUMSI MINUMAN BERALKOHOL PADA REMAJA DI DESA RUMOONG ATAS DUA KECAMATAN TARERAN - Vanessa Manueke, Chayla (Penerbit Lafadz Jaya, 2026)
Alcohol consumption among adolescents in rural Eastern Indonesia has increased due to social, coping motives, and access to traditional drinks like cap tikus, exacerbated by low self-awareness that weakens emotional regulation against peer pressure. This study aimed to examine the influence of self-awareness on motives for alcohol consumption among adolescents in Rumoong Atas Dua Village, Tareran District. Employing a quantitative correlational design with Likert-scale surveys, a population of 96 adolescents aged 18-21 years was purposively sampled to 77 respondents (54 males). Instruments measured self-awareness (41 items) and alcohol motives (43 items), analyzed via Kolmogorov-Smirnov normality test, linearity test, Pearson correlation, and simple linear regression on SPSS (α=0.05). Results revealed a significant positive relationship (r=0.353, p=0.002) with self-awareness influence at β=0.347 (t=3.263, p=0.002; R²=0.124), explaining 12.4% of motive variance. The study concludes that self-awareness significantly influences alcohol motives but with limited effect, necessitating comprehensive self-regulation-based interventions to strengthen its protective function in rural contexts.